Estudo da selfie como narrativa autobiográfica e testemunhal: o caso dos refugiados sírios - Ferreira, Adriana de Oliveira (2017)
The present dissertation aims at analyzing the Syrian refugees’ selfies. When choosing selfies as a means of showing what they are experiencing and how they feel, people going through a civil war open a perspective for us to think this practice as an action that is inserted in their sociopolitical context. It is used to start a dialogue process with people, here referred to as spectators that do not belong in the same context of the narrated fact. The relationship between those people is established by the mise en abyme (the narrative inside that narrative) as well as by the autobiographic testimonial narrative of the person going through the narrated fact. Therefore, those who talk about themselves cannot be dissociated from what is happening. Approaching people that experienced a brutal historical narrative (Syria civil war) to those who did not experience it is to connect two completely different worlds so that they could be shared by means of dialogue. To get to this point, it is necessary that the Viewer do a deconstruction of the word selfie. At the end, an autobiographical narrative and testimony of Syrian refugees creates a mise en abyme between subjects.